PROSES KREATIF DAN PERAN WAKIDJO DALAM KENDHANGAN GAYA SURAKARTA - Risnandar Risnandar (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2014)
The research project titled the Creative and role Wakidjo in Kendhangan Karawitan Surkarta Style to measures for reconstruct a forming process and in progress of Wakidjo as kendang player. Wakidjo is a drummer with experience, a rich drumming vocabulary, and his own style. His style has spread and influenced other drummers. This research is based on three main questions: Who is Wakidjo? What are the factors that have influenced the formation and development of Wakidjo’s drumming? This research aims to reveal Wakidjo’s life, his approach to drumming, and his contribution to the world of Solonese style gamelan music, uses a qualitative methodology. Besides drawing on oral accounts from several informants, it also uses literary sources that concern drumming and gamelan musicians. Several psychological theories are used as a basis for writing a profile about Wakidjo. Among others, this project uses convergence theory from William Stren and theory about the development of talent from Monks and Y. Punberg. The results of this research are divided into several chapters covering Wakidjo’s life and his artistic ability. The form and development of Wakidjo’s individuality have been influenced by many factors, including the social circles in which he lived, his family, and the twists and turns of his life. He has been able to develop his artistry to a high degree through a long process. This process has been affected by both internal factors—such as his talent—and external factors—such as his aesthetic experiences, his interaction with other artists, and the artistic circles in which he has worked. The product of his artistic journey is the style of his drumming. This research concludes that Wakidjo’s existence as one of the foremost drummers in Surakarta has been influenced by several factors, including his surroundings, his talent, his performance experience, his predecessors, gamelan associations, the gamelan circle at the National Indonesian Radio Station (RRI) in Surakarta, the world of the recording industry, and the world of gamelan music education.Keywords: Wakidjo, creative process. kendangan